Correction to: Effects of Bang® Keto Coffee Energy Drink on Metabolism and Exercise Performance in Resistance-Trained Adults: A Randomized, Double-blind, Placebo-controlled, Crossover Study - Patrick S. Harty; Matthew T. Stratton; Guillermo Escalante; Christian Rodriguez; Jacob R. Dellinger; Abegale D. Williams; Sarah J. White; Robert W. Smith; Baylor A. Johnson; Mark B. Sanders; Grant M. Tinsley (Taylor & Francis Group, 2020)
An amendment to this paper has been published and can be accessed via the original article.